1963
DOI: 10.1002/ange.19630752102
|View full text |Cite
|
Sign up to set email alerts
|

Neuere Entwicklungen in der Pteridin‐Chemie

Abstract: Aus der Fiille des experitnentellen Materials der Pteriditi-Chemie werden die wichtigsten Ergebnisse der letztetr zehn Jahre sowie des III. Internationalen Pteridin-Symposiums zusaniniengefapt. Es ivird iiber Synthesen, Reaktionen rind Struktirrprobleme so wie iiber natiirliche Pteridine irnd ihre niogliche biochetnische Bedeutung berichtet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

1970
1970
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 221 publications
0
8
0
2
Order By: Relevance
“…), is located in between the reflectance spectra of the two Colotis species. The spread of the reflectance spectra of orange and red wing areas, from which one and the same pigment (erythropterin; Pfleiderer, 1963;Descimon, 1971) was extracted, is discussed below.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…), is located in between the reflectance spectra of the two Colotis species. The spread of the reflectance spectra of orange and red wing areas, from which one and the same pigment (erythropterin; Pfleiderer, 1963;Descimon, 1971) was extracted, is discussed below.…”
Section: Article In Pressmentioning
confidence: 99%
“…The pigments all appeared to belong to one class, appropriately called the pterins (Descimon, 1975;Kayser, 1985). Leucopterin and isoxanthopterin absorb exclusively in the ultraviolet, and consequently inhomogeneous, scattering substances containing these pterins have a white color; xanthopterin and dihydroxanthopterin absorb in the violet as well, and thus produce a yellow color; and with the blue-absorbing erythropterin an orange or red color remains (Pfleiderer, 1963;Descimon, 1971;Watt, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that the yellow color of these cells is due to sepiapterin (6), a compound that was first isolated from the sepia mutant of Drosophila and was shown to be a 7,8-dihydropterin carrying a lactoyl group at position C-6 (reviewed in Ref. 22). Accumulation of pteridines in the skin of various cyprinid species has also been described (19,23,24), and the main component of these, originally named ichthyopterin, was shown to be 7-oxobiopterin (25,26).…”
mentioning
confidence: 99%
“…some cases the problems of Isolation and characterization are caused by the low concentrations of pteridines in biological samples; they are generally present only in trace amounts (1,2). An exception is the relatively high concentrations which are found in the wings ofPteridae butterflies.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent review of pteridine chemistry up to 1963 is given by Pfleiderer (2). Interesting and more recent aspects of analysis were described in the reports of the pteridines symposia held at Konstanz in 1973 (3) and at La Jolla, California, in 1978 (4), (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%